KONSEP ULAMA PERSPEKTIF AL-QUR’AN: Studi Komparatif Penafsiran Fakhruddin Al-Razi dan Yunan Yusuf - Noor Rizqy Sattariya; Syaifuddin Syaifuddin; Najib Irsyadi (Sekolah Tinggi Ilmu Al-Qur'an Ar-Rahman, 2025)
This study examines the concept of ulama in the Qur'an through a comparative approach to the interpretations of Fakhruddin al-Razi and Yunan Yusuf. The analysis focuses on two verses Q.S. al-Shu‘arâ’`/26:197 and Q.S. Fâtir/35:27–29 with the aim of exploring a broader and deeper understanding of the term ulama. This research employs a qualitative method using a library research approach and a descriptive-comparative technique. The analysis is conducted through the stages of identification, description, and comparison of the interpretations offered by both scholars. The findings reveal that both Fakhruddin al-Razi and Yunan Yusuf define ulama as individuals with deep knowledge that leads to khashyah (reverence and submission) to Allah. Both emphasize the importance of integrating knowledge, practice, and piety in shaping the true character of an ulama. However, they differ in terms of the scope of knowledge and the interpretive approaches applied. Yunan Yusuf sees ulama not only as religious scholars but also as experts in general fields such as science and medicine, as long as their knowledge brings them closer to God, using the adabî-ijtimâ‘î (literary-sociological) approach. In contrast, Fakhruddin al-Razi interprets ulama as those who specialize in religious knowledge and comprehend God's greatness, which fosters piety, using a lughawî (linguistic) approach.